2014
DOI: 10.1152/ajpheart.00462.2014
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 receptor expression in astrocytes is upregulated leading to increased mortality in mice with myocardial infarction-induced heart failure

Abstract: Isegawa K, Hirooka Y, Katsuki M, Kishi T, Sunagawa K. Angiotensin II type 1 receptor expression in astrocytes is upregulated leading to increased mortality in mice with myocardial infarction-induced heart failure. Am J Physiol Heart Circ Physiol 307: H1448 -H1455, 2014. First published September 12, 2014 doi:10.1152/ajpheart.00462.2014.-Enhanced central sympathetic outflow worsens left ventricular (LV) remodeling and prognosis in heart failure after myocardial infarction (MI). Previous studies suggested that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 51 publications
(76 reference statements)
3
30
0
Order By: Relevance
“…The functional significance of the AngII effect on PVN astrocytes is further highlighted by our in vivo studies showing a contribution of PVN astrocytes to the AngII-evoked increase in sympathetic nerve activity and blood pressure. Our results are also consistent with a recent study showing that targeted-deletion of astrocyte AT1 receptors diminished sympathoexcitation in mice with heart failure 22 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The functional significance of the AngII effect on PVN astrocytes is further highlighted by our in vivo studies showing a contribution of PVN astrocytes to the AngII-evoked increase in sympathetic nerve activity and blood pressure. Our results are also consistent with a recent study showing that targeted-deletion of astrocyte AT1 receptors diminished sympathoexcitation in mice with heart failure 22 .…”
Section: Discussionsupporting
confidence: 93%
“…Yet, numerous studies, including our own, have shown AT1 receptor-mediated actions on astrocytes and microglial cells 20, 35 . Conversely, there is more consensus supporting increased AT1 receptor expression in glial cells in pathological conditions, including inflammation, hypertension and heart failure 22, 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a link between AT 1 R and TLR4 in medicating microglial activation in the PVN has been reported (79). Interestingly, AT 1 R is upregulated in glial astrocytes after myocardial infarction, and glial-cell specific deletion of AT 1 R blunted sympathoexcitation in response to myocardial infarction (417). These studies implicate both neuroglial signaling and AT 1 R expression and action in cells other than neurons in the brain as mediating some of the pathological action of ANG II.…”
Section: Regulation Via Pvn At 1 Rmentioning
confidence: 84%
“…Recently, we have demonstrated that targeted deletion of AT 1 R in astrocytes strikingly improved survival with prevention of left ventricular remodeling and sympathoinhibition in myocardial infarction-induced heart failure. 82) From these results, we believe that AT 1 R in astrocytes, not in neurons, have a key role in the pathophysiology of heart failure. Conclusion: Heart failure is a complex syndrome with sympathoexcitation, and no one doubts that excess sympathoexcitation should be the target of treatments for heart failure.…”
Section: Central Mechanisms Of Sympathoexcitation In Heart Failurementioning
confidence: 79%